외국인 근로자의 심리적 행복감 영향요인 - 정한나(Jung, Hanna); 김영숙(Kim, Youngsuk) (지역사회간호학회지, 2020)
Purpose: This study aims to identify related factors of psychological well-being of migrant workers in Korea. Methods: The subjects were 138 migrant workers residing legally in K or B Cities. Data were collected from July 1 to August 31, 2018, using self-report structured questionnaires that were translated into English, Chinese, Vietnamese, and Korean, and were analyzed with descriptive statistics, t-test, ANOVA, Pearson's correlation coefficients and multiple regression. Results: The most important influencing factors on the psychological well-being of migrant workers were social support (β=.36, p<.001), followed by perceived health status (β=.25, p=.001), education (β=-.18, p=.015), and spouse support (β=.16, p=.032). The overall explanatory power was 28.9%. Conclusion: In order to improve the psychological well-being of migrant workers, it is required to develop a nursing approach that may promote the social support, health status, and spouse support, and consider the educational level of migrant workers.